Design and Performance Study of Plate Falling Film Absorber with a Film- inverting Configuration - 崔晓钰; 唐聪; 李美玲 (Zhileng xuebao)
Plate falling film absorber with a film - inverting configuration is a new kind of absorber that combines the plate falling film absorption technique and the film - inverting technique. In this study, the absorber's structure under design condition was determined by building and solving mathematical model of the plate falling film absorption process with film inverting configuration. The heat and mass transfer performances were calculated by the model under different solution flow rates, its inlet concentrations, its inlet temperatures, absorption pressures, and cooling conditions. Then the comparisons were performed between the new designed film - inverting absorber and the designed vertical plate falling film absorber.